FIQH LUGHAH DAN ILMU AL- LUGHAH (Sebuah Kajian Komparatif) - Astuti, Uci Widya (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2024)
Abstract:This article discusses the comparison between Fiqh Lughah and the Science of al-Lughah in the context of Arabic studies. Fiqh Lughah, as a branch of Islamic legal studies, focuses on the understanding and application of language in the context of sharia, while the science of al-Lughah covers the science of Arabic linguistics in general, including the structure, function, and use of language. This study aims to analyze the differences and similarities in the methodologies, objectives, and practical applications of these two fields. With a comparative approach, this study explores how Fiqh Lughah influences the understanding of legal texts and how al-Lughah science contributes to the development of the overall theory of the Arabic language. The results show that although the two share the same Arabic language base, Lughat Fiqh is more focused on the application aspect of law while the al-Lughah science emphasizes more on the theoretical and structural aspects of language. This research provides new insights into understanding the relationship between linguistics and Islamic law and their respective contributions to the study of Arabic.Keywords: Fiqh Lughah, Science of al-Lughah, Arabic language studies, linguistics, Islamic law, methodological comparison. Abstrak:Artikel ini membahas perbandingan antara Fiqh Lughah dan Ilmu al-Lughah dalam konteks studi bahasa Arab. Fiqh Lughah, sebagai cabang dari studi hukum Islam, fokus pada pemahaman dan penerapan bahasa dalam konteks syariah, sedangkan Ilmu al-Lughah mencakup ilmu linguistik Arab secara umum, termasuk struktur, fungsi, dan penggunaan bahasa. Kajian ini bertujuan untuk menganalisis perbedaan dan kesamaan metodologi, tujuan, serta aplikasi praktis dari kedua bidang ini. Dengan pendekatan komparatif, penelitian ini menggali bagaimana Fiqh Lughah mempengaruhi pemahaman teks hukum dan bagaimana Ilmu al-Lughah berkontribusi pada pengembangan teori bahasa Arab secara keseluruhan. Hasil penelitian menunjukkan bahwa meskipun keduanya berbagi basis bahasa Arab yang sama, Fiqh Lughah lebih terfokus pada aspek aplikasi hukum sementara Ilmu al-Lughah lebih menekankan aspek teori dan struktur bahasa. Penelitian ini memberikan wawasan baru dalam memahami hubungan antara linguistik dan hukum Islam serta kontribusi masing-masing terhadap studi bahasa Arab.Kata Kunci: Fiqh Lughat, Ilmu al-Lughah, studi bahasa Arab, linguistik, hukum Islam, komparasi metodologi.